Bimetallic sulfide ZnMoS4-x/C nanocoral synthesized through glucose-assisted supercritical water system and its high performance for lithium-ion batteries. (10th April 2022) - Zhuang, Ji; Zhang, Mengqi; Li, Bo; Zhu, He; Zhao, Xiangyan; Zheng, Qingxin; Xue, Ni; Wang, Lei; Liu, Yang; Tao, Xutang
Abstract: Bimetallic sulfides have been attracted much attention as promising materials due to their excellent electrochemical performance and efficient energy storage in secondary batteries. Here we report ZnMoS4-x compound and associated ZnMoS4-x /C composites synthesized via supercritical water method as anode materials for high-capacity Li ion storage. The one-step preparation of ZnMoS4-x compound and ZnMoS4-x /C composites employing supercritical water as reaction media is easily-accessible, low-cost and environment-benign. Through situ-modifying from glucose carbonization, ZnMoS4-x /C composite with unique nanocoral structural framework retains the large capacity of pure bimetallic sulfides and exhibits improved long-cycle stability as anodes in lithium-ion batteries. Specifically, ZnMoS4-x /C delivers reversible capacity of 931.1 mAh g −1 after 70 cycles at current density of 100 mA g −1 . And at high current density of 1500 mA g −1, it also exhibits an excellent capacity of 640.2 mAh g −1 even after 500 cycles. This work characteristic of environmental and accessible strategy would inspire meaningful impact upon synthesizing functional bimetallic sulfides electrode materials with high electrochemical performances.